The effects of several types of botanical pesticides against whitefly (Bemisia tabaci) on cayenne pepper cultivation in peatlands - Apriani, Rila Rahma; Saputra, Riza Adrianoor; Guna, Ridho Adji (Postgraduate Program - Lambung Mangkurat University (ULM Press Academic), 2023)
Botanical pesticides are supporting sustainable agricultural systems with a focus on the efficiency of pest control and reducing the negative effect of synthetic pesticides. Many plant species such as neem, soursop, and jatropha were found to have the potential to control pests, including whitefly (Bemisia tabaci). B. tabaci is an important pest in cayenne pepper cultivation. This study aims to find botanical pesticides effectiveness against B. tabaci on cayenne pepper growth in peatlands. This study used a one-factor randomized group design method. The factor studied was a pesticide solution (p), p0 as a control we used Abamectin, and 3 types botanical pesticides, p1 = soursop leaf, p2 = neem leaf, and p3 = jatropha leaf, each treatment is repeated 6 times. The results showed that the application of botanical pesticide solution had an effect on mortality and intensity of pest attack. The best treatment in the study was neem leaf pesticide (p2) which caused whitefly mortality of 96.7% and reduce pest attacks intensity to 5,10%.